Functional features of trophic use of carbon sources by pathogenic champignon bacteria (Agaricus bisporus) - T. Ivanova; M. Patyka; T. Tarasiuk (Карантин і захист рослин)
Goal. Purpose. The study of the functional features of pathogenic bacteria, which are isolated from Agaricus bisporus.